Ghungroo - Ali Rizvi (Dastavezi, 2022)
Ghungroo is a film that aims to critically reorient dance in the contemporary cultural landscape of Pakistan, focusing mainly on the lived experiences of Dawood Bhatti, a Kathak dancer. Bhatti tackles the binary representation of gender and thus is emblematic of emergent discourses on gender identity and dance in Pakistan. Ghungroo is the depiction of struggle and success derived from the freedom of a gender-fluid identity, using dance as a subversive medium with the power to explore the boundaries of power and patronage.